Long Range Anticorrelations and Non-Gaussian Behavior of a Leaky Faucet - Penna, T. J. P; de Oliveira, P. M. C; Sartorelli, J. C; Gonçalves, W. M; Pinto, R. D (1995)
We find that intervals between successive drops from a leaky faucet display scale-invariant, long-range anticorrelations characterized by the same exponents of heart beat-to-beat intervals of healthy subjects. This behavior is also confirmed by numerical simulations on lattice and it is faucet-width- and flow-rate-independent. The histogram for the drop intervals is also well described by a Lévy distribution with the same index for both histograms of healthy and diseased subjects. This additional result corroborates the evidence for similarities between leaky faucets and healthy hearts underlying dynamics.